The Effect of Leadership Style, Workload, and Career Level on the Performance Employees of Upt Galang Health Centre - Yendri, Yendri; Titik W, Diana (Universitas Batam, 2023)
This research aims to analyze the effects of leadership style, workload and career level on the performance of UPT employees. Galang Community Health Center. The independent variable in this research is employee performance (Y). The independent variables consist of Leadership Style (X1), Workload (X2) and Career Path (X3). The population is UPT employees. Batam City Galang Community Health Center, 60 employees. The sample was determined using the census method. Data analysis uses multiple linear regression with quantitative methods. The research results indicate that leadership style and workload have a significant effect on employee performance, while career level has an insignificant negative effect on performance. The R Square value is 0.804, meaning that 80.4% of the independent variables are able to explain the dependent variable, the remaining 19.6 are explained by other factors outside the research.